Endophlebectomy of the common femoral vein and arteriovenous fistula creation as adjuncts to venous stenting for post‐thrombotic syndrome. Issue 6 (21st February 2017) - de Wolf, M. A. F.; Jalaie, H.; van Laanen, J. H. H.; Kurstjens, R. L. M.; Mensinck, M. J. S.; de Geus, M. J.; Gombert, A.; de Graaf, R.; Wittens, C. H. A.
Abstract: Background: Good results have been reported for angioplasty and stenting of post‐thrombotic lesions of the iliac and proximal femoral veins. If lesions at the origin of the superficial femoral and profunda veins are stented, the intraluminal synechiae can be pushed against the orifices of inflow vessels, potentially decreasing stent inflow. Surgical disobliteration of the common femoral vein (endophlebectomy) has been suggested to mitigate this problem. Because of a temporary increase in thrombogenicity, this procedure may be accompanied by arteriovenous fistula creation. Methods: Data on consecutive patients treated by hybrid venous reconstruction, between December 2010 and May 2015, were analysed. Standard recording consisted of clinical scoring systems (including Villalta scale) and imaging. Patency was assessed with duplex ultrasonography. Results: Seventy‐six legs (70 patients) were included. Median follow‐up was 379 (range 73–1508) days. Primary, assisted primary and secondary patency rates at 12 months were 51, 70 and 83 per cent respectively. Sixty per cent of loss of primary patency (24 of 40 legs) was related to common femoral vein stenosis, and the rest to rethrombosis. Other complications included wound infection (29 per cent) and lymphatic leak (39 per cent). The Villalta score had decreased by a median of 7 points at 1‐year follow‐up. Conclusion: The combination of venous stenting, endophlebectomy and arteriovenous fistula creation for patients with extensive post‐thrombotic vein damage and severe post‐thrombotic syndrome is feasible. Abstract : Two‐thirds improve